Business conditions analysis - Lewis, John P. (New York : McGraw-Hill, 1959)
This book is aimed primarily at advanced undergraduate courses and at first-year graduate students preparation in economics and does not necessarily extend beyond the usual two-semester introductory sequence.
Includes bibliographical references and index
hza 24/09/2018
Loans
Keywords: Business cycles; Business forecasting